In vitro callus culture and these callus essential oil compositions of ten populations Hypericum scabrum L. from Turkey - Kilic, Omer; Ozdemir, Fethi Ahmet (Progress in Nutrition, 2016)
This study aims to develop in vitro callus from hypocotyl explants of ten different wild populations of H. scabrum growing in Turkey and evaluate the potential of these callus essential oils production with industrial application. Hypocotyl parts of in vitro growing plants used as explants sources. In vitro cultures were established on MS medium supplemented with 2 mg/L 2,4-D + 0.1 mg/L BAP. Some Hypericum taxa callus contains naphthodianthrones, phloroglucinols, tannins, xanthones, phenolic acids and essential oil. According to the HS-SPME/GC-MS analyses, a total of forty-one components were detected in ten H. scabrum calli with relatively high variation in their essential oil composition. Among constituents, α-pinene (7.68-40.20%), β-pinene (1.30-35.74%), limonene (0.02-32.21%), β-ocimene (0.0-37.90%) and germacrene D (0.15-30.55%) were found as the most abundant constituents in studied populations calli essential oils. Results showed that in vitro calli could be a good experimental system for further researches on essential oil production.